The dynamics of the reaction OH+D-2->HOD+D: Crossed beam experiments and quantum mechanical scattering calculations on ab initio potential energy surfaces - Alagia, M; Balucani, N; Casavecchia, P; Stranges, D; Volpi, G; Clary, D; Kliesch, A; Werner, H (1996)
The dynamics of the reaction OH + D2 → HOD + D has been investigated in a crossed molecular beam experiment at a collision energy of 6.3 kcal/mol. From laboratory product angular and velocity distribution measurements, center-of-mass product translational energy and angular distributions were determined. The HOD angular distribution is strongly backward scattered (with respect to the OH direction), which reflects a direct rebound dynamics, and the average fraction of total available energy released into translation is 0.34, indicating a high degree of product internal excitation. These results are compared with the predictions of two different ab initio potential energy surfaces within quantum mechanical scattering calculations based on the rotating bond approximation. It is concluded that a new surface, obtained from large scale high-quality electronic structure calculations, represents a significant improvement with respect to the previous Walch-Dunning-Schatz-Elgersma potential energy surface.